Tools for estimating fake/non-prompt lepton backgrounds with the ATLAS detector at the LHC - Amelung, C.; Angerami, A.; Araujo Ferraz, V.; Armbruster, A.J.; Bahmani, M.; Balz, J.; Barends, K.N.; Bi, R.; Bingul, A.; Burdin, S.; Chiedde, N.; Clavijo Columbie, J.M.; et al. (Journal of instrumentation, 2023)
Measurements and searches performed with the ATLAS detector at the CERN LHC often involve signatures with one or more prompt leptons. Such analysesare subject to `fake/non-prompt' lepton backgrounds, where either a hadron or a lepton from a hadron decay or an electron from a photon conversion satisfies the prompt-leptonselection criteria. These backgrounds often arise within a hadronic jet because of particle decays in the showering process, particle misidentification or particleinteractions with the detector material. As it is challenging to model these processes with high accuracy in simulation, their estimation typically uses data-driven methods.Three methods for carrying out this estimation are described, along with their implementation in ATLAS and their performance.